Balancing learning and knowledge protection in university-industry collaborations. Issue 2 (4th February 2019) - Kunttu, Leena; Neuvo, Yrjö
Abstract : Purpose: The purpose of this study is to examine the tension between learning and protection in university-industry relationships (UIRs) and, in particular, to identify practices that facilitate ways of coping with this tension. Design/methodology/approach: The empirical work for the study is based on a qualitative comparative case analysis of six successful, long-term relationships between industrial technology firms and university research groups in Finland. Findings: The findings of the study reveal that the development of mutual trust, based on personal-level relationships, adaptation and reaching a consensus about the utilization of research results represent the key processes that enable partners to balance learning and protection and lower the informational barriers within the collaboration. Research limitations/implications: The case data have been collected from IT industry, in which the need for knowledge is changing rapidly and the need for learning is typically high. However, generalization of the results may need additional case studies including from other industrial areas. Practical implications: The results highlight a rich set of practices that can support both industrial actors and academics in improving their engagement in collaboration and to facilitate successful knowledge creation and utilization in UIRs. Originality/value: This study extends the existing literature on UIR learning by presenting organizational practices, which help UIR actors to balance learning and protection in their collaboration. Along with mutual trust and adaptation achieved in long-term personal relationships, these practices allow partners to overcome organizational barriers that result from different orientations, attitudes and incentives.